USM BUDDIES ASSISTING INTERNATIONAL STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 17 March 2016 – Universiti Sains Malaysia (USM) has introduced the International Student Buddies (BUDDIES) student volunteers group, to become intermediaries between local and international students studying at USM.